Financial institutions invest $ 300,000 in loans designed using innovations from the Seeing is Believing project in India - CGIAR Platform for Big Data in Agriculture (2021)
De-risking of Dvara E-Registry's credit model attracted funding of more than $ 300,000 for loans issued using outputs from the Seeing is Believing project (also see OCIR).